Experimental evaluation on the effect of electrostatic minimum quantity lubrication (EMQL) in end milling of stainless steels. Issue 2 (4th March 2018) - Huang, Shuiquan; Lv, Tao; Xu, Xuefeng; Ma, Yaliang; Wang, Minghuan
ABSTRACT: The machining of stainless steels is very challenging owing to their high toughness and low thermal conductivity, causing high cutting temperatures and rapid tool wear. Conventionally, metalworking fluids in flood form are used during the process to improve surface quality and tool life; however, their use raises issues including environmental pollution and economic concerns. Therefore, an electrostatic minimal quantity lubrication (EMQL) technology was developed to reduce the consumption of metalworking fluids. EMQL is a near-dry machining technology utilizing the synergetic effects between electrostatic spraying and minimum quantity lubrication (MQL), wherein the lubricant is to apply in a form of fine, uniform and highly penetrable and wettable mist droplets directly to the cutting zone. This study investigates the effect of EMQL in end milling of AISI 304 stainless steel in comparison with dry, wet and MQL machining. The results suggest that EMQL reduces tool wear and cutting force, prolongs tool life considerably and enhances surface finish compared with conventional wet and MQL machining. scanning electron microscopy and Energy-dispersive X-ray spectroscopy analyses show that EMQL considerably reduces adhesive and abrasive wear on the flank face because of the lower friction and heat generation resulting from more efficient entry of the lubricant into the cutting interfaces.